Role of fetal craniotomy in modern day obstetrics: case series - Xess, Somila; Shrivastava, Shipra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Although obstructed labor in vanished from the western world where the destructive operations are obsolete and not needed, in developing countries like India obstructed labor with dead fetus and severe infection is a sad reality, and destructive operations are an essential part of obstetric practice and cannot be wished away. In many situations they should be a preferred option to cesarean delivery which needs much better facilities and greater morbidity. Here authors present a case series of three patients who reported with obstructed labour and IUFD. Fetal craniotomy was done and thus maternal morbidity reduced. Craniotomy offers less postpartum morbidity, lesser expertise and resources and therefore better in cases presenting with obstructed labour and dead baby in developing countries.